Environmental factors influencing the physiological disorders of edema on ivy geranium (Pelargonium peltatum) and intumescences on tomato (Solanum lycopersicum) - Rud, Nicole Ann (Kansas State University, 2010)
Ivy geranium (Pelargonium peltatum L’Herr ex. Ait.) and tomato (Solanum lycopersicum L.) are two economically important greenhouse crops known to be affected by non-pathogenic lesions on leaf tissues. These physiological disorders are often termed edema (oedema) or intumescences, but several other names have been used including enations, non-pathogenic galls or tumors, and neoplasms. These lesions, characterized by small protrusions on leaf tissues that become necrotic over time, are considered to be the result of environmental factors. Our research focused on determining what environmental factors affect these disorders on ivy geranium and tomato. The physiological disorder of ivy geranium is thought to be the result of water uptake exceeding transpiration, resulting in a build-up of water and solutes in leaf tissue that results in the blister-like protrusions in the epidermal layer. Current convention suggests that susceptible plants be grown in an environment that promotes transpiration with low humidity and infrequent watering. Over four experiments, we evaluated the effects of four root medium water contents, five rates of supplemental calcium application and two vapor pressure deficit (VPD) environments on three cultivars of ivy geranium. Our results indicate that high root medium water contents do not increase the incidence of edema on ivy geranium, but increase overall plant growth. Supplemental calcium had no affect on edema or growth, while our VPD results were inconclusive. These results suggest that current convention regarding cultural practices that abate the disorder be revisited. In tomato var. hirsutum ‘Maxifort’, the physiological disorder is characterized by individual epidermal cells swelling, which is unlike the disorder in ivy geranium where solutes build up across a group of epidermal cells. The environmental factors we focused on were two root medium water contents and supplemental UVB light. Our results suggest that root medium water content may play a role in development of tomato intumescences based on visual observation, and UVB light supplementation helps prevent the lesions from forming.
Keywords: Edema; Intumescence; Tomato; Ivy geranium; UVB Light; Water relations; Agriculture, Plant Culture (0479)